Comparison of lens refractive parameters in myopic and hyperopic eyes of 6–12-year-old children - Shang, Jianming; Hua, Yanjun; Wang, Yuliang; He, Ji C.; Zhou, Xingtao; Qu, Xiaomei (Frontiers in Medicine, 2022)
Background/aims To evaluate the influence of cycloplegia on lens refractive parameters in 6–12-year-old children with myopia and hyperopia for exploring the pathogenesis of myopia. Methods One hundred eyes of 100 patients (50 boys) were included. In the myopic group, 50 subjects (25 boys and 25 right eyes) were enrolled with a mean age of 9.20 ± 1.69 years. IOLMaster 700 measurements were performed pre- and post-cycloplegia. The pictures were marked using semi-automatic software. The lens curvature and power were obtained using MATLAB image processing software. Paired and independent sample t-tests were used for data analysis. Statistical significance was set at P < 0.05. Results Anterior and posterior lens curvature radius in myopic eyes were larger than those in hyperopic eyes, both pre- and post-cycloplegia (both P < 0.001). The refractive power in myopic eyes was lower than that in hyperopic eyes without cycloplegia, both pre- and post-cycloplegia (both P < 0.001). The changes in anterior lens curvature and refractive power between pre- and post-cycloplegia in hyperopic eyes were larger than those in myopic eyes (both P < 0.05). No significant difference was found in the change in posterior lens curvature and refractive power after cycloplegia in hyperopic and myopic eyes (P > 0.05). Conclusion Anterior and posterior surfaces of the lens were flatter, and the refractive power was lower in the myopia group than in the hyperopia group. Myopic and hyperopic patients showed a tendency for lens flattening and refractive power decrease after cycloplegia. Hyperopic patients had more changes in anterior lens curvature and refractive power after cycloplegia.